Simulation on Robot Arm Manipulator Modeling using Dynamic Kinematic - Roshahliza, M. Ramli; Nurul Aqilah, Herman; Mohd Azrul Hisham, Mohd Adib (IEEE, 2020)
This simulation shows about analysis of 6 Degrees of Freedom (DOF) Of robotic arm kit generated by Robo Analyzer software. Moreover, this visual simulation consisted of mathematical elements that can animate the mechanical of motion for a robot manipulator. Nowadays, there was a lot of Unmanned Ground Vehicle (UGV) had been equipped with manipulator but the lack of stability in pick and place object was the main problem in safety issues especially in a safety application. For example, safety authorities need to lift picric acid by using less vibration and correct trajectory to avoid an explosion. Therefore, the main objective of this research is to identify the value of the position and orientation of each joint correctly because all these values were needed to be used by the controller to tackle stability issues. Besides, parameters to conduct the simulation can solve forward kinematic of the robot in the form of a 3D model which can determine the suitable motor with enough power and torque that can be used by each of the joints. This Robo Analyzer used a geometrical approach which is first, it used Denavit Hartenberg parameters to determine end effectors. Next, Robo Analyzer used forward and inverse dynamic analysis to get torque values. The simulation results clearly show the effectiveness of Robo Analyzer software to generate a simulation of the coordinate for each joint, joint parameter, and joint torque that is needed to select a suitable motor with enough torque. In other words, the significance of this research is, by using Robo Analyzer, the user can forecast the hardware simulation result before applying it in the real situation because the visual stimulation can animate the motion of the robot from the beginning until its last position.